Searching the Missing Link for Assuring the Quality of Enacted School Curriculum - Sumaiya, Bushra; Masih, Aejaz (JOURNAL OF INDIAN EDUCATION, 2018)
Today’s fast-paced globalisation has put schools under extreme pressure to transform learners into an efficient workforce and to deliver quality education and quality learning outcomes. Although rigorous efforts have been made to ensure educational quality and students’ learning by prescribing an elaborate curriculum for general school education, wide gaps exist between the prescribed curriculum and how it has been enacted in schools that is, what has been stated in the face of prescribed curriculum is yet to be implemented in the true sense of the word. Although the schools and stakeholders in education are investing so much in terms of time, effort, and resources to assure the quality of enacted school curriculum, they are still in search of the missing link for assuring the educational quality. Their major concern is what more could be done to assure the quality of enacted school curriculum? The present paper proposes that the quality of enacted school curriculum could be assured by making the students’ learning engagement an integral component of the learning process. Students’ learning engagement is the active involvement and participation of students in learning activities of the school. It is a crucial academic construct which has great potentiality to assure educational quality and to deeply engage students in the cognitive and co-cognitive activities of the school. However, the potentiality of this construct is often overlooked during curricular transactions in the classroom. In this regard, the present paper puts forth a theoretical model for assuring the quality of enacted school curriculum through students’ learning engagement.